2018
DOI: 10.1088/1361-6560/aaa614
|View full text |Cite
|
Sign up to set email alerts
|

Average glandular dose in paired digital mammography and digital breast tomosynthesis acquisitions in a population based screening program: effects of measuring breast density, air kerma and beam quality

Abstract: The main purpose was to compare average glandular dose (AGD) for same-compression digital mammography (DM) and digital breast tomosynthesis (DBT) acquisitions in a population based screening program, with and without breast density stratification, as determined by automatically calculated breast density (Quantra). Secondary, to compare AGD estimates based on measured breast density, air kerma and half value layer (HVL) to DICOM metadata based estimates. AGD was estimated for 3819 women participating in the scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 170 publications
(367 reference statements)
1
28
2
1
Order By: Relevance
“…Both the AGD from DM and DBT were within the limits set in the European Guidelines (238). It was also shown that the AGD from DBT was 33 % higher for women with non-dense breasts and 8 % higher for women with dense breasts (165). Therefore, the increase in AGD for DBT is lower for women with dense breasts.…”
Section: Radiation Dose Estimates For Dm and Dbtmentioning
confidence: 60%
See 3 more Smart Citations
“…Both the AGD from DM and DBT were within the limits set in the European Guidelines (238). It was also shown that the AGD from DBT was 33 % higher for women with non-dense breasts and 8 % higher for women with dense breasts (165). Therefore, the increase in AGD for DBT is lower for women with dense breasts.…”
Section: Radiation Dose Estimates For Dm and Dbtmentioning
confidence: 60%
“…Paper III showed that when using DBT, the AGD was about 24 % higher compared to DM, increasing from 1.74 to 2.10 mGy per view on average (165). Both the AGD from DM and DBT were within the limits set in the European Guidelines (238).…”
Section: Radiation Dose Estimates For Dm and Dbtmentioning
confidence: 85%
See 2 more Smart Citations
“…Hence, there is no need to worry that the use of this FDA-approved technique would be associated with any harm to the patients [ 35 ]. Osteras et al investigated the average glandular dose in paired FFDM and DBT acquisitions in a population-based screening program (including 3819 women) and found that the mean dose for FFDM, DBT, and Combo was 1.72, 2.09, and 3.81 mGy, respectively [ 36 ]. Our study observed similar results.…”
Section: Discussionmentioning
confidence: 99%